Preventing blood-induced joint damage with the use of intra-articular iron chelators: an experimental study in rabbits - EROL, BÜLENT (SPRINGER, 2009)
This animal model was designed to evaluate the effect of intra-articular iron-chelator treatment in the prevention of blood-induced joint disease. Thirty domestic male rabbits were divided into three equal groups. One milliliter of homologous blood was injected into the left knee of each rabbit in groups 1 and 2. In the second group, 0.1 ml desferroxamine mesilate (DM) was also injected to the blood. In group 3, the animals received injections of 0.1 DM which was mixed with equal amounts of sterile saline solution. The joints were injected three times each week for 12 weeks. At the end of 12 weeks, the knee joints of each rabbit were examined. The synovium in group 1 was found statistically significantly thicker than in group 2. Obvious erosion and ulceration of the cartilage were seen in all joints in group 1 and absent in group 2. Iron-chelator treatment reduced the formation of blood-induced joint damage in rabbit knees by inhibiting the iron-catalyzed formation of destructive oxygen metabolites that has an effect on joint cartilage and synovium.
Keywords: Blood; Cartilage damage; Oxidative stress; Iron chelator; HEMOPHILIC SYNOVITIS; IN-VITRO; MODEL; THERAPY